Suitability of Drinking Water Sources from Nyaruzinga Wetland for Domestic Use in Bushenyi Municipality, Uganda - Muhangane, Lauben; Nkurunungi, John Bosco; Yatuha, Jane; Andama, Morgan (Scientific Research Publishing, 2017)
This study determined the physico-chemical and bacterial quality of raw (bo rehole, springs, wells) and tap water sources from Nyaruzinga wetland for domestic use in Bushenyi Municipality. Forty samples of raw water were ran domly collected from Kacuncu, Kyeitembe and Kikuba tributaries of the wet land and 40 samples of tap water generated from the same wetland were ran domly drawn from Ishaka, Nyakabirizi and Central divisions of the Munici pality. The samples were analyzed for apparent colour (AC), turbidity, elec trical conductivity (EC), total hardness, pH, Total iron, residual alum, free re sidual chlorine and faecal coliforms using standard methods and their values compared with standard local UNBS (2008) and international WHO (2011) drinking water quality guidelines. The results showed that the mean pH of the protected spring below Kikuba Hill (5.21); the AC (Pt/Co) of the borehole be low Bweranyangi Junior School (17.28) and the surface well below Nyandozo Primary School (157.58) both situated in Kacuncu as well as the free residual chlorine (mg/L) in tap water at Kanyamabona Trading Centre, Ishaka division (0.192) were below the standard values of WHO (pH, 6.0 - 8.0; free residual chlorine, 0.2 - 0.5) and UNBS (AC, <15). The electrical conductivity, EC (µS/cm) and total hardness (mg/L) of all the selected water sources were within the WHO standards The residual alum (mg/L) in all the tap water sources was also within the WHO guideline (faecal coliform count (≤3 TCUs). Only the tap water at Kanyamabona Trad ing Centre recorded mean faecal coliform counts (0.25 TCUs) beyond the WHO standard (0 TCU). Hence the quality of tap water within the munici pality tapped from Nyaruzinga wetland was generally better than the raw drinking water sources (borehole, springs, wells) from the same wetland. Thus the use of piped tap water by the urban inhabitants as opposed to raw water sources needs to be promoted to increase access to safe water
Keywords: Bacterial Load; Bushenyi Municipality; Drinking Water Sources; Physico-Chemical Parameters